Impacts of the novel coronavirus variants on the Philippine stock market - Abante, Joshua I.; Estudillo, Jonna P. (Quezon City School of Economics, University of the Philippines Diliman, 2022)
The COVID 19 pandemic has brought broad socioeconomic effects that stretch far beyond the health sector. With those effects come opportunities to examine the implications of major health crises on stock markets. This paper investigates the effects of the Variants of Concern (VOC) designation of the SARS-CoV-2 virus on the Philippine Stock Market by employing the Event Study Methodology. The results show significant reactions from the firms in the Philippine Stock Exchange index (PSEi), generally positive abnormal returns on stock prices, and the presence of sectoral effects.
Thesis (BS Economics) - - University of the Philippines Diliman
Includes bibliographical references.
Keywords: COVID-19 (Disease).; COVID-19 (Disease) -- Economic aspects